Assessment of Passenger Satisfaction for Local Train Services on the Madiun–Solo Route Based on the Customer Satisfaction Index (CSI) Method - Ipung Wisnu Triono; Hera Widyastuti (Universitas Islam Raden Rahmat, Malang, 2026)
Passenger satisfaction is an important indicator of service performance in public transportation, particularly for local railway services that support regional mobility. This study aims to evaluate passenger satisfaction with the local train operating on the Madiun–Solo route using the Customer Satisfaction Index (CSI) method. The research was conducted in the operational area of DAOP 7 Madiun and involved 250 passengers as respondents. Data were collected through field surveys using structured questionnaires that assessed six service dimensions: tangibles, reliability, responsiveness, assurance, empathy, and accessibility. The CSI analysis results indicate an overall satisfaction index of 69.50%, which falls within the “satisfied” category, suggesting that the service generally meets passenger expectations. Nevertheless, several service attributes, including service frequency, seating arrangement, ticketing convenience, and feeder transport availability, show relatively lower satisfaction levels and require improvement. These findings emphasize the importance of continuous service enhancement to improve passenger experience and increase the attractiveness of local rail services. The results are expected to serve as a reference for transportation operators and policymakers in developing sustainable railway services along the Madiun–Solo corridor.